1941
DOI: 10.1128/jb.42.2.173-192.1941
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Nicotinic Acid in Bacterial Metabolism

Abstract: In our previous publications Grossowicz 1938, 1939) we showed that nicotinic acid plays an essential part in the carbohydrate metabolism of certain members of the colon-typhoid group of bacteria-particularly Salmonella paratyphi A, Shigella dysenteriae and some strains of the Flexner type of dysentery. Our results indicated that nicotinic acid was not a growth factor in the limited sense, because growth occurred in its absence, but that it played the part of a codehydrase making available to the organism a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1945
1945
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Previous work also suggested that the production of NA through nicotinamidases might enhance microbial infectivity instead of acting as a growth factor for microorganisms; hence, the inhibition of nicotinamidases might not affect their growth. 33,34 This assay supports our hypothesis that the NA in contaminated cell culture medium was converted from NAM by microbial nicotinamidases. Our study aimed to provide a broadbased sterility testing method for CTPs but not a method that is capable of identifying different microbial species.…”
Section: The Production Of Na Is Caused By Microbial Nicotinamidasessupporting
confidence: 83%
“…Previous work also suggested that the production of NA through nicotinamidases might enhance microbial infectivity instead of acting as a growth factor for microorganisms; hence, the inhibition of nicotinamidases might not affect their growth. 33,34 This assay supports our hypothesis that the NA in contaminated cell culture medium was converted from NAM by microbial nicotinamidases. Our study aimed to provide a broadbased sterility testing method for CTPs but not a method that is capable of identifying different microbial species.…”
Section: The Production Of Na Is Caused By Microbial Nicotinamidasessupporting
confidence: 83%
“…The literature records instances of the depression of bacterial growth by the inclusion of glucose in the medium. Glucose has usually been shown to exert its effect by interfering with amino acid metabolism (Kligler and Grossowicz, 1941;Kligler et al, 1943;Shaposhnikov and Tauson, 1948;Forbes and Sevag, 1951). Jordan (1952) believed the inhibition of growth of Pasteurella septica, when cultured with glucose in the medium, was due to the accumulation of inhibitory amounts of H202.…”
Section: Discussionmentioning
confidence: 99%
“…Threonine is a polar proteinogenic amino acid involved in lipid metabolism and protein synthesis ( 60 , 61 ). Two other metabolic intermediates, nicotinic acid and choline, which play central roles in bacterial metabolism, were also identified ( 62 , 63 ). Because the laser energy density was chosen to mimic relatively low ice grain impact speeds of 4 to 6 km/s ( 41 ), elemental ions of masses <18 unified atomic mass unit (u), such as C + or N + , were not created in detectable quantities and thus are not expected to be abundant in impact ionization mass spectra of bacterial cells encountered in this speed regime.…”
Section: Discussionmentioning
confidence: 99%